2014
DOI: 10.1016/j.jecp.2014.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Relations among prospective memory, cognitive abilities, and brain structure in adolescents who vary in prenatal drug exposure

Abstract: This investigation examined how prospective memory (PM) relates to cognitive abilities (i.e., executive function, attention, working memory, and retrospective memory), and brain structure in adolescents who vary in prenatal drug exposure (PDE). The sample included 105 (55 female, 50 male) urban, primarily African American adolescents (mean age 15.5 years) from low socioeconomic status (SES) families; 56% (n=59) were prenatally exposed to drugs (heroin and/or cocaine) and 44% (n=46) were not prenatally exposed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 88 publications
1
24
0
Order By: Relevance
“…Conversely, young people who have experienced poverty are comparable with norms on tests of verbal memory and executive function (Robey et al, 2014). Performance on tests of working memory is variable (Robey et al, 2014;Walker et al, 2005). In the homeless category, Saperstein et al (2014) found impaired performance compared to norms in their sample on tests of general cognitive functioning, executive function, working memory, attention, and verbal memory.…”
Section: Comparisons To Normsmentioning
confidence: 95%
See 2 more Smart Citations
“…Conversely, young people who have experienced poverty are comparable with norms on tests of verbal memory and executive function (Robey et al, 2014). Performance on tests of working memory is variable (Robey et al, 2014;Walker et al, 2005). In the homeless category, Saperstein et al (2014) found impaired performance compared to norms in their sample on tests of general cognitive functioning, executive function, working memory, attention, and verbal memory.…”
Section: Comparisons To Normsmentioning
confidence: 95%
“…The performance of young people who have experienced poverty tends to be below the normative averages in the domains of general cognitive functioning (Campbell, Ramey, Pungello, Sparling, & Miller-Johnson, 2002;Howell, Lynch, Platzman, Smith, & Coles, 2006;Walker, Chang, Powell, & Grantham-McGregor, 2005; but see Ivanovic et al, 2000) and sustained attention (Coles, Platzman, Lynch, & Freides, 2002;Robey, Buckingham-Howes, Salmeron, Black, & Riggins, 2014). Conversely, young people who have experienced poverty are comparable with norms on tests of verbal memory and executive function (Robey et al, 2014). Performance on tests of working memory is variable (Robey et al, 2014;Walker et al, 2005).…”
Section: Comparisons To Normsmentioning
confidence: 98%
See 1 more Smart Citation
“…The effects of IUDE can persist over the developmental continuum into adulthood, and the deficits seen across populations can vary (Bard, Coles, Platzman, & Lynch, 2000;Bhide & Kosofsky, 2009;BuckinghamHowes, Mazza, Wang, Granger, & Black, 2016;Derauf, Kekatpure, Neyzi, Lester, & Kosofsky, 2009;Jaeger, Suchan, Schölmerich, Schneider, & Gawehn, 2015;Nadebaum, Anderson, Vajda, Reutens, & Wood, 2012;Pulsifer, Radonovich, Belcher, & Butz, 2004;Robey, Buckingham-Howes, Salmeron, Black, & Riggins, 2014); however, executive functions, social and emotional delays, and integration of social cues and rules appear to be the most prevalent issues seen in the clinical experience of the current authors.…”
Section: Introductionmentioning
confidence: 78%
“…The Heschl’s gyri is found related to auditory processing and semantic task [ 41 ], and its abnormalities has been shown as one of the main reasons for the impairment of human cognitive abilities [ 42 , 43 ]. Since memory and cognitive abilities are the two important components that are commonly assessed in IQ tests [ 44 ], changes of GM/WM tissues in these ROIs may affect the quantification of human intelligence. In a supplementary experiment, we treat age as an independent type of features and further combine it with GM and WM features by using multi-kernel SVR, for the purpose of investigating whether it will affect the performance of our estimators.…”
Section: Discussionmentioning
confidence: 99%